Tako-Tsubo Cardiomyopathy in a Patient with Advanced Colorectal Adenocarcinoma - Yusuf Kasirye; Ihab B. Abdalrahman (Case Reports in Medicine)
Transient left ventricular dysfunction syndrome (TLVDS), or Tako-Tsubo cardiomyopathy (TC), is a clinical entity in which patients present with features of acute coronary syndrome, electrocardiogram abnormalities, and transient left ventricular (apical or mid-ventricular) dysfunction. Patients usually recover from this condition four to six weeks after the event. The etiology or triggering factors of TC remains unknown. Various triggering factors have been associated with this syndrome, with one of the most recent being malignancies. In this case report we present a postmenopausal female with underlying advanced malignancy who presented with TC. This is consistent with a recent hypothesis that in addition to currently known triggering factors, malignancies might well trigger TC in the context of a stressor or paraneoplastic phenomenon.